2017
DOI: 10.1103/physrevlett.118.134501
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Quantum and Classical Flows in Quantum Turbulence in TheT=0Limit

Abstract: Tangles of a quantized vortex line of initial density L(0)∼6×10^{3}  cm^{-2} and a variable amplitude of fluctuations of flow velocity U(0) at the largest length scale are generated in superfluid ^{4}He at T=0.17  K, and their free decay L(t) is measured. If U(0) is small, the excess random component of the vortex line length first decays as L∝t^{-1} until it becomes comparable with the structured component responsible for the classical velocity field, and the decay changes to L∝t^{-3/2}. The latter regime alw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Despite this, many recent theoretical works involving superfluid Bose-Einstein condensates (BECs) have suggested that largescale, same-sign Onsager vortex clusters play an important role in 2D quantum turbulence [8][9][10][11][12][13][14][15][16][17]. In superfluids, much of the focus to date has been on decaying-rather than driventurbulence [9,[11][12][13][14][17][18][19][20][21][22][23][24], since this scenario removes the complications of stirring. A variety of concepts have been applied to the problem, including holographic duality [25,26] and nonthermal fixed points [27][28][29].Experimentally, BECs provide unprecedented opportunities to investigate 2D superfluid turbulence due to the high degree of controllability available in these systems.…”
mentioning
confidence: 99%
“…Despite this, many recent theoretical works involving superfluid Bose-Einstein condensates (BECs) have suggested that largescale, same-sign Onsager vortex clusters play an important role in 2D quantum turbulence [8][9][10][11][12][13][14][15][16][17]. In superfluids, much of the focus to date has been on decaying-rather than driventurbulence [9,[11][12][13][14][17][18][19][20][21][22][23][24], since this scenario removes the complications of stirring. A variety of concepts have been applied to the problem, including holographic duality [25,26] and nonthermal fixed points [27][28][29].Experimentally, BECs provide unprecedented opportunities to investigate 2D superfluid turbulence due to the high degree of controllability available in these systems.…”
mentioning
confidence: 99%
“…This suggests that distribution of velocity or vorticity may obey a different scaling law or power law for length scales larger than the average distance l between domain walls. This situation is similar to the hierarchy in quantum turbulence, where the Kolmogorov or semi-classical power law is realized over length scales larger than the average distance between vortex lines and a different power law is expected for smaller length scales [37,38]. In the field of quantum turbulence, the connection regime between the two scaling regimes has also received a lot of attention and should be discussed further qualitatively here.…”
Section: Summary and Discussionmentioning
confidence: 59%
“…Pure Superfluid Turbulence in He II Driven at Small and Large Scales. Quantitative data on steady-state and decaying pure superfluid He II turbulence have been obtained by Golov and coworkers (34)(35)(36). They injected negative ions into the experimental ‡ Although the energy spectrum beyond ℓ Q has not yet been measured, a hint of possible k −3 scaling at high k appears in the Andreev reflection data (figure 13 in ref.…”
Section: Pure Superfluid Turbulencementioning
confidence: 99%